Metabolic Reprogramming Induces Macrophage Polarization in the Tumor Microenvironment - Wang, Shilin; Liu, Guohong; Li, Yirong; Pan, Yunbao (Frontiers in Immunology, 2022)
Macrophages are one of the most important cells in the innate immune system，they are converted into two distinct subtypes with completely different molecular phenotypes and functional features under different stimuli of the microenvironment: M1 macrophages induced by IFN-γ/lipopolysaccharides and M2 macrophages induced by IL-4/IL-10/IL-13. Tumor-associated macrophages (TAMs) differentiate from macrophages through various factors in the tumor microenvironment (TME). TAMs have the phenotype and function of M2 macrophages and are capable of secreting multiple cytokines to promote tumor progression. Both tumor cells and macrophages can meet the energy needs for rapid cell growth and proliferation through metabolic reprogramming, so a comprehensive understanding of pro-tumor and antitumor metabolic switches in TAM is essential to understanding immune escape mechanisms. This paper focuses on the functions of relevant signaling pathways and cytokines during macrophage polarization and metabolic reprogramming, and briefly discusses the effects of different microenvironments and macrophage pathogenicity, in addition to describing the research progress of inhibitory drugs for certain metabolic and polarized signaling pathways.